Binding through branding: an investigation into the impact of brand experience and brand image on consumers’ perception of trust in the context of the UK financial services sector - Moin, S.M.A. (2016)
The purpose of this thesis is to understand the impact of brand experience and brand image on consumers’ perceptions of trust in the context of the UK financial services sector. Since the financial crisis in 2008, trust has been an issue for financial services brands with scandals surfacing continually such as the “Libor Scandal” in 2012 (BBC News, 2013); the manipulation of foreign exchange markets by proprietary traders in large banking institutions (Financial Times, 2014); a number of banks being fined a total of £2.7 bn (BBC News, 2013) and so on. In these kinds of scenarios of declining trust, it is of paramount importance that financial services brands not only focus on their brand identity but also consistently deliver a favourable brand experience and build a strong brand image to contribute in the restoration of trust in financial services. Therefore, this study makes a timely contribution by providing a nuanced understanding of how and to what extent brand experience and brand image impact consumers’ perception of trust in the context of financial services from an interdisciplinary perspective.